Duration of Antimicrobial Therapy in Community Acquired Pneumonia: Less Is More - Marilia Rita Pinzone; Bruno Cacopardo; Lilian Abbo; Giuseppe Nunnari (The Scientific World Journal)
Community acquired pneumonia (CAP) represents the most common cause of infection-related morbidity and mortality worldwide. Appropriate treatment of CAP is challenging and sometimes limited by the availability to obtain rapid and timely identification of the etiologic agent in order to initiate or deescalate the correct antimicrobial therapy. As a consequence, prescribers frequently select empiric antimicrobial therapy using clinical judgment, local patterns of antimicrobial resistance, and, sometimes, individual patient expectations. These issues may contribute to prolonged courses of inappropriate therapy. In this review, we discuss the evidence and recommendations from international guidelines for the management of CAP and the clinical trials that specifically addressed duration of antimicrobial therapy for CAP in adults. In randomized controlled trials comparing the clinical efficacy of a short-course antimicrobial regimen versus an extended-course regimen, no differences in terms of clinical success, bacterial eradication, adverse events, and mortality were observed. The use of biomarkers, such as procalcitonin, to guide the initiation and duration of antimicrobial therapy may reduce total antibiotic exposure and treatment duration, healthcare costs, and the risk of developing antimicrobial resistance. In clinical practice, antimicrobial stewardship interventions may improve the management of CAP and may help in reducing treatment duration. Sometimes “less is more” in CAP.